(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
This text discusses aspects of the creation of the theatrical show Agamenon or - How much is the life of a man? at Palmas (TO). This is done with regard to memory and historical imagery present in the composition of the work. Methodologically, the text emerges from the articulation between the director’s memories, historical and social data that supported the creation, images of the show’s presentation, excerpts from the dramaturgy of the work and theoretical concepts as it came from analysis. It resulted from the research that the articulation between fiction and reality and the scenic occupation of spaces of social conflicts favor the emergence, in addition to the physicality of the place, of symbolic and imaginary flows from and about the theatrical place.